Deep Learning in Physics Education: Exploring the Potential of Mindful, Meaningful, and Joyful for a Better Learning Experience - Sumarni, Ria Asep; Okyranida, Indica Yona (Navigation Physics : Journal of Physics Education, 2025)
This article explores the synergistic potential of integrating the Deep Learning  approach with the Mindful, Meaningful, and Joyful learning paradigm to enhance physics education. Traditional physics instruction often faces "fundamental barriers" in human learning, leading to a lack of student engagement and a decline in expert-like confidence. Despite efforts to improve teaching methods, significant progress in student learning outcomes remains difficult to achieve. We argue that Deep Learning , with Intelligent Tutoring System (ITS) capabilities in personalization, adaptation, and interactive simulation, can act as a powerful driver to foster mindful, meaningful, and joyful learning experiences in physics. Mindful learning enhances cognitive and emotional well-being, meaningful learning promotes deep understanding and relevance, and joyful learning nurtures intrinsic motivation and creativity.  A comprehensive review of the latest literature (2015-2025) reveals that intelligent Deep Learning -powered tutoring systems, adaptive learning environments, virtual laboratories, personalized feedback mechanisms, and gamification strategies can collectively transform physics pedagogy. This integration encourages increased student engagement, better conceptual understanding, critical thinking, problem-solving skills, and more positive emotional involvement, thereby creating a more effective and sustainable learning journey. It is concluded that the holistic framework integrating Deep Learning with this pedagogical philosophy offers a promising path to address long-standing challenges in physics education.